أنواع الإختبار في تعليم اللغة العربية - Nur Kholis (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
Test language is one of the tools used to make the measurements tosomething abstract, such as the ability to think, the ability toremember, writing skills, speech and other language skills.Forms of the language testis very diverse, so are the approach ituses. Test language can be differentiated based on ability orcomponent that is the target language is used as focus measuremastery level. Judging from the way the preparation of test, can bedifferentiated a standardized test and a teacher-made test. The testlanguage distinguished by a test that was developed based on adifferent view to understanding the nature of language consists ofdiscrete test, intregatif test, pragmatic test and communicative test